Segmentation of plate coupling, fate of subduction fluids, and modes of arc magmatism in Cascadia, inferred from magnetotelluric resistivity. (11th November 2014) - Wannamaker, Philip E.; Evans, Rob L.; Bedrosian, Paul A.; Unsworth, Martyn J.; Maris, Virginie; McGary, R. Shane
Abstract Five magnetotelluric (MT) profiles have been acquired across the Cascadia subduction system and transformed using 2‐D and 3‐D nonlinear inversion to yield electrical resistivity cross sections to depths of ∼200 km. Distinct changes in plate coupling, subduction fluid evolution, and modes of arc magmatism along the length of Cascadia are clearly expressed in the resistivity structure. Relatively high resistivities under the coasts of northern and southern Cascadia correlate with elevated degrees of inferred plate locking, and suggest fluid‐ and sediment‐deficient conditions. In contrast, the north‐central Oregon coastal structure is quite conductive from the plate interface to shallow depths offshore, correlating with poor plate locking and the possible presence of subducted sediments. Low‐resistivity fluidized zones develop at slab depths of 35–40 km starting ∼100 km west of the arc on all profiles, and are interpreted to represent prograde metamorphic fluid release from the subducting slab. The fluids rise to forearc Moho levels, and sometimes shallower, as the arc is approached. The zones begin close to clusters of low‐frequency earthquakes, suggesting fluid controls on the transition to steady sliding. Under the northern and southern Cascadia arc segments, low upper mantle resistivities are consistent with flux melting above the slab plus possible deep convective backarc upwelling toward the arc. In central Cascadia, extensional deformation is interpreted to segregate upper mantle melts leading to underplating and low resistivities at Moho to lower crustal levels below the arc and nearby backarc. The low‐ to high‐temperature mantle wedge transition lies slightly trenchward of the arc.